Comparison of the review models and regulatory timelines of seven countries participating in the ECOWAS-MRH initiative: identifying opportunities for improvement - Owusu-Asante, Mercy; Darko, Delese Mimi; Seaneke, Seth; Nacoulma, Aminata; Traore, Oula Ibrahim Olivier; Adeyeye, Mojisola Christianah; Akinyemi, Abayomi; Assane, Coulibaly; Clamoungou, Clarisse Épse Kaul Meledje; Ndao, Oumy Kalsoum; Kande, Rokhaya Ndiaye; Komeh, James; et al. (Frontiers in Medicine, 2025)
IntroductionNational regulatory medicines authorities (NRAs) are mandated to ensure timely access to high-quality, safe and efficacious medical products, primarily achieved through a marketing authorisation procedure established in each country. The aim of this study which was similar to that carried out in the SADC and EAC regions, was to assess and compare the review models and regulatory timelines of seven of the national medicines regulatory authorities (NRAs) of the Economic Community of West African States-Medicines Regulatory Harmonization (ECOWAS- MRH) initiative, Burkina Faso, Cote d’Ivoire, Ghana, Nigeria, Senegal, Sierra Leone and Togo, in order to identify opportunities for improvement. The NRAs were included in the study based on their active participation in the regional initiative.MethodsThe Optimising Efficiencies in Regulatory Agencies (OpERA) questionnaire was completed by each of the NRAs to facilitate the assessment of the review models and regulatory timelines.ResultsThe authorities employ the three types of scientific review models, verification review (type 1), abridged review (type 2) and full review (type 3). Five of the NRAs deploy the fast track/priority review model in which a rapid assessment is carried out to obtain pharmacological, marketing/commercialisation, pharmacovigilance and additional clinical trial information. In Cote d’Ivoire, the priority review is used by the authority for WHO-prequalified medicines and stringent regulatory authority-approved medicines. Data requirements for the applications are essentially the same among the seven authorities. Applicants are required to provide a completed dossier in the common technical document format to support an application for marketing authorisation irrespective of the review model. Differences were noted with regard to comparison of the key features of the regulatory systems for medicines: as previously mentioned, five of the authorities required submission of a CPP with the application or before authorization. 25% of the review staff were physicians in five of the NRAs. Furthermore, procedures to allow the company response time to be measured and differentiated in the overall processing time were not available in Burkina Faso. In addition, there were differences reported in the targets for the key milestones in the full review process. These issues ultimately led to differences in the overall approval times for medicines that were processed via the full review pathway. The extent of the scientific review is dependent on the type of review model that is deployed in processing the application. Recommendations for improvement for the seven regulatory authorities include: publication of targets and timelines for key milestones; recognition of the ECOWAS-MRH initiative as a reference to expedite their approvals at the country level; and development of robust information technology systems.ConclusionThis comparative study of the review models and regulatory timelines of countries participating in the ECOWAS-MRH initiative has highlighted both the similarities among the authorities and also the differences to be addressed in order to improve upon the regulatory systems in these countries.